2016
DOI: 10.2139/ssrn.2854858
|View full text |Cite
|
Sign up to set email alerts
|

Talent in Distressed Firms: Investigating the Labor Costs of Financial Distress

Abstract: The importance of skilled labor and the inalienability of human capital expose firms to the risk of losing talent at critical times. Using Swedish microdata, we document that firms lose workers with the highest cognitive and noncognitive skills as they approach bankruptcy. In a quasi-experiment, we confirm that financial distress drives these results: following a negative export shock caused by exogenous currency movements, talent abandons the firm, but only if the exporter is highly leveraged. Consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 25 publications
(38 reference statements)
0
24
0
1
Order By: Relevance
“…Normally, inventors of sold innovation leave the firm with a much higher intensity. Inventors also tend to leave a company after it files for bankruptcy-that is, there is a loss of talent and human capital (Graham et al, 2016;Baghai et al, 2017). Interestingly, coefficients associated with I(PatentBeingSold) lit × I(InBankruptcy) it are negative and marginally significant.…”
Section: Evidence From Human Capital Reallocation While Actively Selmentioning
confidence: 99%
“…Normally, inventors of sold innovation leave the firm with a much higher intensity. Inventors also tend to leave a company after it files for bankruptcy-that is, there is a loss of talent and human capital (Graham et al, 2016;Baghai et al, 2017). Interestingly, coefficients associated with I(PatentBeingSold) lit × I(InBankruptcy) it are negative and marginally significant.…”
Section: Evidence From Human Capital Reallocation While Actively Selmentioning
confidence: 99%
“…We use career data for five years before and after the liquidation event, to make sure that the endpoints of the leads and lags are not a mixture of further leads and lags. Since it has been shown that talented workers tend to leave their companies when these approach bankruptcy (Baghai et al, 2017), we count as affected employees all those who were employed in the relevant fund in a two-year window prior to the event. This avoids the selection bias that could be induced by considering only those still working at the fund when it is wound up.…”
Section: [Insert Figure 6]mentioning
confidence: 99%
“…The acceptance of a glass cliff appointment can be considered a risky career decision. Numerous studies on career decision making and occupational choice (Baghai et al, 2018;Brown and Matsa, 2016;Ye, 2014) have focused on riskiness of career options, risk preferences and risk behaviors, showing that risk status of the job influences occupational choice. From a risk-taking perspective, the glass cliff phenomenon reveals an intriguing paradox; women are risk averse but choose risky leadership jobs.…”
Section: Literature Review and Theoretical Developmentmentioning
confidence: 99%